2022
DOI: 10.1387/ijdb.210186dk
|View full text |Cite
|
Sign up to set email alerts
|

Cortical interneuron development: a role for small Rho GTPases

Abstract: GABAergic interneurons control cortical excitation/inhibition balance and are implicated in severe neurodevelopmental disorders. In contrast to the multiplicity of signals underlying the generation and migration of cortical interneurons, the intracellular proteins mediating the response to these cues are mostly unknown. We have demonstrated the unique and diverse roles of the Rho GTPases Rac1 and 3 in cell cycle and morphology in transgenic animals where Rac1 and Rac1/3 were ablated specifically in cortical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…During their tangential migration, interneurons follow a stereotypic cyclic type of movement (Bellion et al, 2005). Efforts to uncover the intracellular mediators responsible for the response of CINs to environmental cues, have demonstrated that Rho-GTPases play significant roles in interneuron development through diverse functions (Corbetta et al, 2005; Corbetta et al, 2009; de Curtis, 2014; Kalemaki et al, 2018; Kounoupa and Karagogeos, 2022; Pennucci et al, 2016; Tivodar et al, 2015; Vidaki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…During their tangential migration, interneurons follow a stereotypic cyclic type of movement (Bellion et al, 2005). Efforts to uncover the intracellular mediators responsible for the response of CINs to environmental cues, have demonstrated that Rho-GTPases play significant roles in interneuron development through diverse functions (Corbetta et al, 2005; Corbetta et al, 2009; de Curtis, 2014; Kalemaki et al, 2018; Kounoupa and Karagogeos, 2022; Pennucci et al, 2016; Tivodar et al, 2015; Vidaki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%